A Meta-Analysis and Systematic Review on the Association between Human Papillomavirus (Types 16 and 18) Infection and Esophageal Cancer Worldwide. - Jing Wang; Lei Zhao; Han Yan; Juanjuan Che; Li Huihui; Wu Jun; Bing Liu; Bangwei Cao (PLoS ONE)
Background Esophageal cancer is a common and aggressive malignant tumor. This study aimed to investigate the association between human papillomavirus (HPV) Types 16 and 18 and esophageal carcinoma (EC) in the world population by conducting a meta-analysis. Materials and methods Computerized bibliographic and manual searches were performed to identify all eligible literatures between 1982 and 2014. PUBMED (http://www.ncbi.nlm.nih.gov/pubmed/) and CNKI (http://www.cnki.net/) were the primary sources of case-control studies, and key words used include human papillomavirus, HPV, esophageal, esophagus, cancer, carcinoma, and tumor. All searches were performed by reviewing articles and abstracts cited in the published systematic reviews and case-control studies. Prospective studies that reported relative risk (RR) estimates with 95% CIs for the association between HPV and EC were included. Results Thirty-three randomized studies were identified, and the main features of these trials were included in this systematic review. HPV infection rate in the EC group was 46.5%, while HPV infection rate in the control group was 26.2% (OR = 1.62; 95% CI, 1.33-1.98). In China, the merger OR value was 1.62 (95% CI: 1.26-2.07); while in the Asian region, the merger OR value was 1.63 (95% CI: 1.29-2.04). There were statistical differences in HPV testing due to different detection methods such as PCR, IHC and ISH. In the PCR detection group, the merger OR value was 1.61 (95% CI: 1.33-1.95). Conclusions These results indicate that HPV infection and the incidence of EC are closely associated.